2022
DOI: 10.3390/biomedicines10112734
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Viral Respiratory Infections during the COVID-19 Pandemic Using the FilmArray Respiratory Panel

Abstract: This study was conducted to evaluate the distribution of respiratory viral pathogens in the emergency department during the coronavirus disease 2019 (COVID-19) pandemic. Between May 2020 and September 2022, patients aged between 0.1 and 98 years arrived at the emergency department of Asia University Hospital, and samples from nasopharyngeal swabs were tested by the FilmArrayTM Respiratory Panel (RP). SARS-CoV-2 positivity was subsequently retested by the cobas Liat system. There were 804 patients for whom the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…However, the three most frequently identified viruses in children's respiratory infections in the literature are HRV/EV, RSV, and If A [19,32,33]; this pattern was similarly affirmed in our study.…”
Section: Discussionsupporting
confidence: 88%
“…However, the three most frequently identified viruses in children's respiratory infections in the literature are HRV/EV, RSV, and If A [19,32,33]; this pattern was similarly affirmed in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Most studies have found comparably low rates of viral co-infection in adult populations as those we present here. For example, Chen and Er (2022) characterized FilmArray™ RP results from 804 Emergency Department patients in Taiwan, with 27.9% having positive results, 5.3% of patients having co-infection, but only two co-infections involving SARS-CoV-2, with the plurality of co-infections involving Adenovirus and Rhino/Enterovirus (42%) ( Chen and Er, 2022 ). However, these authors did little to examine the rates of specific viral co-infections relative to the frequency each virus was encountered, or to explore correlations between the incidence of specific viral co-infections.…”
Section: Discussionmentioning
confidence: 99%
“…Horemheb-Rubio et al (2022) conducted such an examination of respiratory viral interactions from 2010-2019 in Europe found relatively few synergistic viral interactions, such as between influenza H3N2 and parainfluenza virus 4 or HCoV-NL63 and parainfluenza virus 1, and predominantly viral exclusion between influenza and RSV, rhinovirus and most parainfluenza viruses (Horemheb-Rubio et al, 2022). However, such an analysis has not been conducted on a pediatric population, which have been shown to have higher rates of respiratory viral co-infection (Dao et al, 2021;Chen and Er, 2022;Krumbein et al, 2023), in general, nor been conducted since the beginning of the COVID-19 pandemic and therefore systematically assessed such viral co-infection dynamics in patients with SARS-CoV-2. The resurgence of respiratory viruses seen over the past two Northern Hemisphere winter seasons represents a unique opportunity to study their co-infection rates normalized to background mono-infection.…”
Section: Introductionmentioning
confidence: 99%
“…Specimens were cultured on Blood agar, Chocolate agar, MacConkey agar and two Sabouraud dextrose agar (SDA) plates (Oxoid, UK) by semi-quantitative technique, plates were incubated aerobically for 24-48 hours at 37°C, one plate of SDA was incubated at 28°C and the other at 37°C, both were examined each other day up to two weeks. Sputum, ETA and BAL cultures were considered positive if ≥10 6 , ≥10 5 and ≥10 4 CFU/mL were detected respectively. Presence of mixed growth of Neisseria spp., diphtheroids, alpha-hemolytic streptococci, or staphylococci was considered as normal flora.…”
Section: Sample Processingmentioning
confidence: 99%
“…Therefore, prompt identification of causative agents and initiation of proper antimicrobial therapy are urgently needed to improve the patient's prognosis. Nucleic acid detection tests have gained popularity because of the rapid turnaround as well as the wide panel of pathogens that can be detected [4,5]. On this basis, syndromic testing has been implemented in most microbiology laboratories worldwide, where multiple agents are tested simultaneously through a single test.…”
mentioning
confidence: 99%